Digital Marketing Transformation of Pempek Culinary Creative Economy through Instagram, TikTok, and Shopee - Maharani, Aliyyah; Sartika, Indira; Aidil Adha, Muhammad Rafi; Panorama, Maya (BIMA Journal (Business, Management, & Accounting Journal), 2025)
Purpose: This study aims to examine the transformation of the creative economy in the culinary subsector—specifically Palembang's traditional pempek—through the application of digital marketing on platforms such as Instagram, TikTok, and Shopee. Methodology: Using a qualitative empirical approach, data was collected through in-depth interviews, observations, and documentation from 15 pempek businesses in Palembang City. Results: Findings show that 92% of businesses experienced increased revenue and 88% reported higher sales after implementing digital marketing strategies. Findings: Additionally, 85% of respondents acknowledged that social media platforms effectively introduced pempek to younger audiences, contributing to cultural preservation. Novelty: This study offers a new perspective by linking digital transformation and visual storytelling with the preservation of traditional culinary heritage. Originality: Unlike prior studies, this research uniquely integrates cultural branding within digital content strategies, demonstrating how digital marketing not only drives business growth but also sustains local identity. Conclusion: Digital marketing plays a strategic role in enhancing the visibility and profitability of traditional culinary MSMEs while supporting the intergenerational transmission of cultural values. Type of Paper: Qualitative Empirical Research Paper.